2016
DOI: 10.1016/j.celrep.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Synaptophysin 1 Clears Synaptobrevin 2 from the Presynaptic Active Zone to Prevent Short-Term Depression

Abstract: Release site clearance is an important process during synaptic vesicle (SV) recycling. However, little is known about its molecular mechanism. Here we identify self-assembly of exocytosed Synaptobrevin 2 (Syb2) and Synaptophysin 1 (Syp1) by homo- and hetero-oligomerization into clusters as key mechanisms mediating release site clearance for preventing cis-SNARE complex formation at the active zone (AZ). In hippocampal neurons from Syp1 knockout mice, neurons expressing a monomeric Syb2 mutant, or after acute b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 57 publications
(99 reference statements)
1
48
1
2
Order By: Relevance
“…Synaptobrevin also interacts with synaptophysin in the synaptic vesicles with six synaptophysin molecules binding to synaptobrevin dimers to form a hexameric ring that directionally orients synaptobrevin toward the presynaptic membrane . Exocytosed synaptobrevin and synaptophysin homo‐ or hetero‐oligomerize into clusters which clears synaptobrevin from the active zone preventing short term depression …”
Section: Discussionmentioning
confidence: 99%
“…Synaptobrevin also interacts with synaptophysin in the synaptic vesicles with six synaptophysin molecules binding to synaptobrevin dimers to form a hexameric ring that directionally orients synaptobrevin toward the presynaptic membrane . Exocytosed synaptobrevin and synaptophysin homo‐ or hetero‐oligomerize into clusters which clears synaptobrevin from the active zone preventing short term depression …”
Section: Discussionmentioning
confidence: 99%
“…This we attribute to two factors. First, in some studies, the glycine was replaced by residues that should not increase the structural rigidity of the TMD 10, 44, 45 . Second, toxins were used in some studies to inhibit the exocytosis supported by the endogenous VAMP2 but in such systems remaining endogenous TMD may dimerize and compensate for the effects of the studied mutations 8, 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Using genetically-encoded reporters of SV cargo in conjunction with super-resolution microscopy, it was demonstrated that freshly deposited cargo was freely diffusible within the plasma membrane, but was prevented from leaving the presynapse by the presence of adaptor proteins and potentially other unidentified factors which retarded diffusion (Gimber et al, 2015 ). Interestingly, the iTRAP synaptophysin has recently been proposed to aid clearance of sybII from active zone regions during action potential stimulation (Rajappa et al, 2016 ). This suggests that a number of SV cargo clustering mechanisms participate in forming and maintaining the readily retrievable pool.…”
Section: How Does Cargo Clustering Integrate With Known Endocytosis Mmentioning
confidence: 99%